The dependency on central government funding of decentralised health systems: experiences of the challenges and coping strategies in the Kongwa District, Tanzania - Frumence, Gasto (BioMed Central, 2014)
BACKGROUND: Decentralised health systems in Tanzania depend largely on funding from the central government to run health services. Experience has shown that central funding in a decentralised system is not an appropriate approach to ensure the effective and efficient performance of local authorities due to several limitations. One of the limitations is that funds from the central government are not disbursed on a timely basis, which in turn, leads to the serious problem of shortage of financial resources for Council Health Management Teams (CHMT). This paper examines how dependency on central government funding in Tanzania affects health activities in Kongwa district council and the strategies used by the CHMT cope with the situation. METHODS: The study adopted a qualitative approach and data were collected using semi-structured interviews and focus group discussions. One district in the central region of Tanzania was strategically selected. Ten key informants involved in the management of health service delivery at the district level were interviewed and one focus group discussion was held, which consisted of members of the council health management team. The data generated were analysed for themes and patterns. RESULTS: The results showed that late disbursement of funds interrupts the implementation of health activities in the district health system. This situation delays the implementation of some activities, while a few activities may not be implemented at all. However, based on their prior knowledge of the anticipated delays in financial disbursements, the council health management team has adopted three main strategies to cope with this situation. These include obtaining supplies and other services on credit, borrowing money from other projects in the council, and using money generated from cost sharing. CONCLUSION: Local government authorities (LGAs) face delays in the disbursement of funds from the central government. This has necessitated introduction of informal coping strategies to deal with the situation. National-level policy and decision makers should minimise the bureaucracy involved in allocating funds to the district health systems to reduce delays.